Improvement of Near Vision for Low Vision Patients in National Eye Healthcare Center Cicendo Eye Hospital 2010-2011 - Muhammadnur Rachim Enoch; Ine Renata Musa; Titing Nurhayati (Althea Medical Journal, 2014)
Background: “Low vision” is a term used refer to a person having a visual acuity of less than 6/18 (20/60) to light perception (LP). People with low vision can still be treated to perceive or see objects, although several limitations occur.  Treatments for people with low vision include either optical or non-optical devices. This research aims to reveal visual acuity for near vision that can serve as corrective benchmark after devices for near vision are given.Methods: This is a retrospective descriptive research, using medical records from  the National Eye Healthcare Center, Cicendo Eye Hospital, for the period of August 2010–September 2011 as the subject of the research. Approximately 475 patients were listed, 263  female and 212  male. The number of  patients with low vision given with corrective device for near vision were 81 patients.Results: The result showed that visual acuity was corrected after corrective devices  for near vision with the size of 1–10 M were given.Conclusions: The highest of overall corrections or improvements for near vision are  the one under the category of “severe visual impairment”.Key words: low vision, optical devices, visual acuity  Peningkatan Penglihatan Jarak Dekat Pada Penderita“ Low Vision” di RS Mata Nasional Cicendo 2010–2011 LatarBelakang: "Low vision" adalah istilah yang mengacu pada seseorang yang memiliki ketajaman visual kurang dari 6/18 (20/60) dengan persepsi cahaya. Orang dengan low vision masih dapat diobati untuk melihat benda meskipun dengan berbagai keterbatasan. Pengobatan terhadap penderita low vision meliputi perangkat optik atau non-optik.. Penelitian ini bertujuan untuk menggambarkan ketajaman visual penglihatan dekat yang dapat berfungsi sebagai pedoman perbaikan setelah perangkat diberikan.Metode: Penelitian ini merupakan penelitian deskriptif retrospektif dengan menggunakan rekam medis dari Pusat Mata Nasional Kesehatan, RS Mata Cicendo, periode Agustus 2010–September 2011 sebagai subjek penelitian. Sekitar 475 pasien yang terdaftar terdiri atas 263 perempuan dan 212 laki-laki, 81 diantaranya diberikan perangkat korektif untuk penglihatan dekat.Hasil: Ketajaman visual dapat diperbaiki setelah dilakukan pemberian perangkat korektif untuk penglihatan jarak dekat dengan ukuran 1–10 M.Simpulan: Peningkatan penglihatan jarak dekat terbaik adalah pada kelompok low vision yang termasuk kategori “gangguan penglihatan berat”.Kata kunci: low vision, perangkat optik, ketajaman visual DOI: 10.15850/amj.v1n2.355